Kejenuhan Belajar Sejarah Kebudayaan Islam (SKI) Siswa Kelas X Di MAN 1 Agam Kecamatan Tanjung Raya - Riri Maria Fitri; Iswantir M; Salmi Wati; Wedra Aprison (Jurnal Riset Sosial Humaniora dan Pendidikan, 2023)
The background of the authors conducting this research, because in learning the history of Islamic culture students are not eager to listen and pay attention to the teacher in the learning process, students receive learning from the teacher using the lecture method. It was at this time that the signs that students were bored with learning SKI began to be seen, when learning took place there were students who were lazy to study, students tended to be busy, sleeping in class, and talking with their desk mates when the teacher explained the material so that students did not focus on learning. The purpose of this study was to find out the characteristics of the saturation and the factors that cause the boredom of learning SKI experienced by students of class X at MAN 1 Agam, and to find out how to overcome the saturation of learning SKI for students of class X at MAN 1 Agam. This study uses a qualitative approach that is field research (field research) with data collection techniques through observation and interviews. The key informants were class X students and the supporting informants were class X Islamic Cultural History subject teachers and school principals. Then the writer performs data analysis with data reduction, displays data, and then provides conclusions from a study. Based on the research results it was found that; (1) The characteristics of students who experience learning burnout in Islamic Cultural History (SKI) at MAN 1 Agam are: decreased motivation to learn, feel weak and get tired quickly, and have difficulty concentrating and easily forget in learning. (2) Factors that cause boredom in studying the history of Islamic culture are physical factors/physical fatigue, motivational factors in learning, methods that do not vary/monotone, inadequate facilities and infrastructure, study hours and lack of recreation and entertainment. (3) Ways to overcome the saturation of learning Islamic cultural history can be done in various ways, namely: approaching students, applying various learning methods, evaluating at the end of each lesson, and making physical changes to the room.